PengembanganKawasanWisataAlamBukitKasihBerdasarkanPreferensi Pengunjung - Triska E. Rintjap; Martina A. Langi; Hengki D. Walangitan (COCOS, 2017)
ABSTRACTThe purpose of this study was to determine the development prospect of Bukit KasihKanonang recreation area basd on visitors’ preferences. Methods use for this study includeddireg observation and interviews to be filled into the questionnaires. Result showed that inaddition to compettion from other recreational sites, challenges arisen from Bukit KasihKanonang mainly came from internal management such as infrastructure maintenance,garbage management, souvenir selling, security, lack of playing grounds, landscapearchitecture, local flora and fauna, and community empowerment to meet the tourism activityof Bukit Kasih Kanonang.Keywords: Bukit Kanonang Kasih, ecotourism, Visitor Preferences